COMPARISON OF THE MODEL CRITICAL DISCOURSE ANALYSIS BY MILLS AND FAIRCLOUGH AT ONLINE MEDIA IN CASE REPORTING OF “IKAN ASIN” - Syarifa Rafiqa (Universitas Indraprasta PGRI, 2019)
Abstract: This study examines how the relationship between gender language and ideology is constructed in media texts, and aims to interrogate a small number of articles taken from the most widely read online editions of national newspapers in Indonesia regarding online media reporting on the harassment of women in the